Genetic variability of mutant rice (Oryza sativa) genotype induced by gamma rays - ISHAK ISHAK (Society for Indonesian Biodiversity, 2023)
Abstract. Ishak I. 2023. Genetic variability of mutant rice (Oryza sativa) genotype induced by gamma rays. Biodiversitas 24: 3300-3306. Rice seeds of Sidenuk cultivars were irradiated by gamma rays creating a broad spectrum of genetic variability among individual plants at M3 generation progeny. Gamma Irradiated seeds created Mutation among the somatic cells population in mature embryos at M1 generations. Somatic cell mutation influenced the genetic structures of gametes cells formation on gametogenesis at M1 plants. Observation of M2 plants showed that black and brown colors of rice's pericarp were found with rice's lemma, and palea color was different compared to the wild type (Sidenuk cultivars). Seven plants with black rice pericarp colors out of 330 were obtained at M2 plants. Chlorophyll mutation was observed at M4 generation; the results showed that chimera, green, and albino leaf blade was obtained in several individual plants. There were also the variability of Palea and lemma colors among individual plant such as green, white, and purple. The cellular biology approach will explain these mutations before molecular biology identification is made.